Emotional burnout syndrome influence on the functional state of the teacher - Arystanbay, A.; Tykezhanova, G.M. (Fundamental and Experimental Biology, 2023)
Nowadays, the role of psychosocial work-related factors is increasing both in the production and non-production areas, which are predisposing to the development of psycho-emotional overstrain, professional stress and burnout. Emotional burnout is associated with psychological discomfort of events, tension, anxiety, loss of life meaning and a tendency to suicide. It manifests itself in the deformation of professional development, personality destruction, in a decrease in the duration and quality of life and the productivity of professional activity. As it is known, professional activity, including the professional environment, affects the state and emotions of the worker, causing a change in the assessment of the situation and in the actions of a person in accordance with the requirements of the activity and their capabilities. Socio-economic changes, taking place in society, cause new requirements for specialists in almost all professions, including teachers. Teachers should possess not only professional knowledge, skills, and abilities, moreover they should have special abilities and personality characteristics that provide flexibility and dynamism of professional behavior. High levels of neuropsychic and emotional stress are related to teachers’ occupations, and as a result, health problems develop. The issue of teachers developing emotional burnout syndrome is addressed in this article. Teachers who are gradually losing energy show signs of emotional debilitation, personal dispassion, physical fatigue, and a decrease of job satisfaction. The paper also presents a theoretical and practical research of emotional burnout syndrome among teachers, the peculiarities of the presentation and factors of emotional burnout are indicated.